Analisis Motivasi Belajar Siswa SD Dalam Pembelajaran Daring di Masa Pandemi Covid-19 Melalui Aplikasi Quizizz - Verellya Caesa Paksi; Aliyatun Nazirah (UM Purwokerto Press, 2021)
The spread of the Covid-19 virus that has swept across the world has caused changes in various aspects, one of which is a change in the learning process, which was previously face-to-face, now learning during the pandemic is carried out online both in elementary, junior high, high school, and even in universities. In online learning, of course, there are many problems faced by students, teachers, and parents. One of the problems that arise is that educators are less able to innovate in making online learning media so that it causes students to experience a decrease in motivation and activity in learning, therefore there is a need for solutions to increase learning motivation, especially for elementary students. One of the media platforms used to increase children's motivation in online learning is by using the Quizziz application. The Quizizz application is one of the fun online learning application media that can be accessed by students and teachers easily and the use of the Quizziz application in giving quizzes to students is one of the targets of students to be even more active in learning and to provide additional learning motivation when learning online today.